Preparation of gulabjamun from buffalo milk khoa/dough incorporated with trisodium citrate - PRAJAPATI, P S; THAKUR, P N; UPADHYAY, K G (The Indian Journal of Animal Sciences, 2013)
Effects of incorporation of trisodium citrate in varying concentrations during khoa and dough making on the quality of gulabiamun were studied. Composition, penetration value and springiness of gulabjamuns were not affected significantly by the use of trisodium citrate, whereas flavour and sugar absorption characteristics improved significantly under similar conditions. Softness and sensory quality of gulabjamun could be improved with the addition of 0.5% trisodium citrate in milk during khoa making.